A comparative study on structural and optical properties of ZnO nanoparticles prepared by three different synthesis methods. (2021) - Rajput, Preasha; Vashishtha, Pargam; Gupta, Govind; Kamni,
Abstract: The structural and optical properties of ZnO nanoparticles synthesized by Combustion method, Co-Precipitation and Hydrothermal method have been studied. The synthesized products were characterized by X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM), UV–Visible Spectroscopy (UV–Vis) and Photoluminescence (PL). The XRD studies revealed that synthesized nanoparticles were crystalline with a hexagonal wurtzite phase. TEM revealed the formation of almost spherical shaped particles. The presence of functional groups and the chemical bonding was confirmed by the FTIR spectra. The UV–Vis absorption spectra indicated absorption peaks in the UV region and band gap values of 3.088 eV, 3.189 eV and 3.177 eV were obtained for samples synthesized by three different routes and designated as (a), (b) and (c), respectively. From PL study the defect mediated orange red emission was observed which indicated that the dominant defect types were the interstitial oxygen ions inside the grain. In addition, the highest relative intensity was found for hydrothermally synthesized nanoparticles and since this method of preparation produced better yield it can be applied for producing better luminescent materials.